(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article considers the theory of generations of William Strauss and Neil Howe and presents its characteristics. It summarizes the influence of political, social and economic changes on the formation of values of certain groups of generations defined by scientists. Presented is the religious choice of those born in the period from 1965 to 2010. It is established that among Generation Y there is a growing number of those who do not identify themselves with religious tradition. The difference between the values of generations has been established: a high percentage of non-religious representatives in Generations Y and Z. The impact of religious values on the difference in their social and personal attitudes, which affect attitudes towards family, work and religion, was proved